Managing knowledge hiding behaviors in Chinese enterprises: the mediating effects of power dynamics losses - Liu, Yi; Liu, Chao; Spolaor, Riccardo; Chen, Shuaishuai (Frontiers in Psychology, 2025)
This paper investigates the influence of power dynamics on knowledge-hiding (KH) behaviors in Chinese enterprises. Data were collected through questionnaires from 342 respondents. Structural equational modeling was performed to analyze the relationships among the perceived value of knowledge (PVK), loss of knowledge power (LOKP), and KH. The findings indicate that PVK is positively related to LOKP, and LOKP mediates the relationship between PVK and KH. However, several hypothesized relationships were not supported, highlighting the complexity of the mechanism underlying KH. The findings suggest that while power dynamics influence KH behaviors, their effects may vary across different contexts and conditions. This study enhances the current understanding of knowledge hiding by contextualizing power dynamics in the Chinese context. It offers a nuanced understanding of when and how knowledge power affects employees' willingness to share or withhold knowledge.